Patellar Tendon Rupture 12 Years after ACL Reconstruction with BPTB Autograft - Christopher C. Paiz; Dustin L. Richter (Case Reports in Orthopedics)
We present a case of a 33-year-old male with a history of anterior cruciate ligament reconstruction (ACLR) with bone-patellar tendon-bone (BPTB) autograft and prior ipsilateral hamstring harvest, who presented with a complete patella tendon rupture (PTR) 12 years after ACLR. The patient underwent a successful patellar tendon (PT) repair augmented with Achilles tendon allograft and cerclage with nonabsorbable suture tape. PTR after ACLR with BPTB autograft is rare, particularly in patients over a decade out from the index procedure, but can occur. This case report highlights a novel technique for PT repair following BTB ACLR in a hamstring deficient knee.